IMPLEMENTASI PROGRAM DOJO SAFETY MAN DI SMK NEGERI 2 SALATIGA: Indonesia, Inggris - Muhammad Aqil Albieruni; Sutiman (Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University, 2025)
Abstract The objectives of this study are to: (1) describe the Dojo Safety Man program, (2) find out the barriers to the implementation of the Dojo Safety Man program, and (3) find out the solutions to the barriers to the implementation of the dojo safety man program at SMK Negeri 2 Salatiga. This research is a descriptive qualitative research. Data collection techniques used surveys and interviews. The research subjects were three instructors of Dojo Safety Man at SMK Negeri 2 Salatiga. The results of this study are (1) the dojo safety man program at SMK Negeri 2 Salatiga is described from 3 aspects: aspects of planning standards with industry results 58.33% space standards 100% instructor teacher standards and 87.5% material standards, aspects of program implementation with 15 minutes with the think, talk, and work method, aspects of evaluation and follow-up by applying the material to the school environment. (2) The obstacles of the program are: incomplete information, tools, and practice materials, difficulty organizing schedules, and a limited number of dojo safety man instructor teachers. (3) Solutions to overcome obstacles by gradually completing the existing shortcomings and asking for help from the industry for the development of the dojo safety man. The schedule can be overcome by coordinating between departments in using the room alternately and making internal training at school to train teachers to become dojo safety man instructors at SMK Negeri 2 Salatiga. Abstrak Tujuan penelitian ini adalah untuk: (1) mendeskripsikan program dojo safety man, (2) mengetahui hambatan pelaksanaan program dojo safety man, dan (3) mengetahui solusi dalam menghadapi hambatan pelaksanaan program dojo safety man di SMK Negeri 2 Salatiga. Penelitian ini merupakan penelitian deskriptif kualitatif. Teknik pengumpulan data menggunakan survei dan wawancara. Subjek penelitian adalah tiga guru instruktur dojo safety man SMK Negeri 2 Salatiga. Hasil penelitian ini adalah (1) program dojo safety man di SMK Negeri 2 Salatiga dideskripsikan dari 3 aspek: aspek perencanaan standar dengan industri hasilnya 58,33% standar ruang 100% standar guru instruktur dan 87,5% standar materi, aspek pelaksanaan program dengan waktu 15 menit dengan metode think, talk, and work, aspek evaluasi dan tindak lanjut dengan menerapkan materi ke lingkungan sekolah. (2) hambatan program yaitu: belum lengkapnya informasi, alat dan bahan praktik, kesulitan mengatur jadwal dan keterbatasan jumlah guru instruktur dojo safety man. (3) Solusi mengatasi hambatan dengan bertahap melengkapi kekurangan yang ada dan meminta bantuan pihak industri untuk pengembangan dojo safety man. Jadwal dapat diatasi dengan koordinasi antar jurusan dalam penggunaan ruang secara bergantian dan membuat pelatihan secara internal di sekolah untuk melatih guru untuk menjadi instruktur dojo safety man di SMK Negeri 2 Salatiga.